A new species of Achalinus (Squamata: Xenodermidae) from Trang An Landscape Complex, Ninh Binh Province, Vietnam - Luu, Vinh Quang; Ziegler, Thomas; van Ha, Nghia; van Lo, Oanh; Hoang, Tuoi Thi; Ngo, Hanh Thi; Le, Minh Duc; Tran, Dung Hoang; Nguyen, Truong Quang (Zootaxa, 2020)
We describe a new snake of the genus Achalinus based on an adult female specimen from Ninh Binh Province, Vietnam. Achalinus tranganensis sp. nov. is differentiated from its congeners genetically and by a unique combination of the following characters: 1) maxillary teeth 29; 2) suture between the internasals distinctly longer than that between the prefrontals; 3) loreal distinctly wider than high, extending from the nasal to the eye; 4) dorsal scales in 25–23–23 rows, keeled; 5) two pairs of prefrontals; 6) supralabials six; 7) infralabials six; 8) temporals 2+3, the two anterior temporals in contact with eye; 9) ventrals 171; 10) subcaudals 73+, unpaired; 11) cloacal plate entire; 12) dorsum in preservative reddish to greyish brown above; 13) the lower part of head side and chin region somewhat paler than the dorsum; 14) venter greyish cream, with the anterior region of each ventral and subcaudal somewhat darker. Based on molecular comparisons using a fragment of the mitochondrial cytochrome c oxidase subunit I (COI), the new species differs from other members of the genus by at least 11.8%. This discovery increases the number of Achalinus species known from Vietnam to seven.